Circulating microRNA Biomarkers of Thiazide Response in Hypertension - Lakshmi Manasa S. Chekka; Marwa Tantawy; Taimour Langaee; Danxin Wang; Rolf Renne; Arlene B. Chapman; John G. Gums; Eric Boerwinkle; Rhonda M. Cooper‐DeHoff; Julie A. Johnson (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Thiazide diuretics are the second most frequently prescribed class of antihypertensives, but up to 50% of patients with hypertension have minimal antihypertensive response to thiazides. We explored circulating microRNAs (miRNAs) in search of predictive biomarkers of thiazide response. Methods and Results We profiled 754 miRNAs in baseline plasma samples of 36 hypertensive European American adults treated with hydrochlorothiazide, categorized into responders (n=18) and nonresponders (n=18) on the basis of diastolic blood pressure response to hydrochlorothiazide. miRNAs with ≥2.5‐fold differential expression between responders and nonresponders were considered for validation in 3 cohorts (n=50 each): hydrochlorothiazide‐treated European Americans, chlorthalidone‐treated European Americans, and hydrochlorothiazide‐treated Black individuals. Different blood pressure phenotypes including categorical (responder versus nonresponder) and continuous diastolic blood pressure and systolic blood pressure were tested for association with the candidate miRNA expression using multivariate regression analyses adjusting for age, sex, and baseline blood pressure. After quality control, 74 miRNAs were available for screening, 19 of which were considered for validation. In the validation cohort, miR‐193b‐3p and 30d‐5p showed significant associations with continuous SBP or diastolic blood pressure response or both, to hydrochlorothiazide in European Americans at Benjamini‐Hochberg adjusted P<0.05. In the combined analysis of validation cohorts, let‐7g (odds ratio, 0.6 [95% CI, 0.4–0.8]), miR‐142‐3p (odds ratio, 1.1 [95% CI, 1.0, 1.2]), and miR‐423‐5p (odds ratio, 0.7 [95% CI, 0.5–0.9]) associated with categorical diastolic blood pressure response at Benjamini‐Hochberg adjusted P<0.05. Predicted target genes of the 5 miRNAs were mapped to key hypertension pathways: lysine degradation, fatty acid biosynthesis, and metabolism. Conclusions The above identified circulating miRNAs may have a potential for clinical use as biomarkers for thiazide diuretic selection in hypertension. Registration URL: ClinicalTrials.gov. Unique identifiers: NCT00246519, NCT01203852, NCT00005520.